Kedudukan Dan Hak Waris Perempuan Dalam Sistem Hukum Adat Bilateral Pada Masyarakat Muslim (Studi Kasus di Desa Mekarwangi, Kota Bogor, Jawa Barat) - Ulvia Albab; Haidar Bawasie; Revalina Aulia Putri (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study examines the position and inheritance rights of women within the bilateral customary law system among Muslim communities in Mekarwangi Village, Bogor City, West Java. Legal pluralism in Indonesia including Customary Law, Islamic Law (inheritance law), and Western Civil Law creates normative tensions that directly affect women’s standing in inheritance. In bilateral or parental societies there is no distinction between patrilineal and matrilineal descent, so in theory women have equal standing with men in claiming inheritance rights. However, in everyday practice the values held by Muslim communities shape inheritance distribution patterns that do not always align with bilateral principles. This study employs empirical legal research with a qualitative approach, using in-depth interviews and participant observation. The findings indicate that in Mekarwangi Village there is a hybridization of bilateral customary norms, where residents tend to combine them with customary deliberation (musyawarah). Women’s position in inheritance in the study area has improved, although structural inequalities remain in control of land and productive assets. The study recommends harmonizing regulations and strengthening community-based legal awareness to ensure gender justice in the inheritance system.